Influence of a positive family history of both type 2 diabetes and PCOS on metabolic and endocrine parameters in a large cohort of PCOS women - Lerchbaum, Elisabeth; Schwetz, Verena; Giuliani, Albrecht; Obermayer-Pietsch, Barbara (European journal of endocrinology, 2014)
Objective There is evidence suggesting a strong genetic background of polycystic ovary syndrome (PCOS). We aim to study the metabolic and endocrine characteristics of PCOS women with and without a family history (FHx) of type 2 diabetes mellitus (T2DM) and PCOS. Design Cross-sectional study. Methods We analysed the association of T2DM FHx and PCOS FHx with metabolic and endocrine parameters in 714 PCOS women. Results A positive FHx of T2DM and PCOS were prevalent in 36.8 and 21.4% of PCOS women respectively. We found an independent association of T2DM FHx with central fat accumulation, obesity, prediabetes, metabolic syndrome (MS), insulin resistance, low HDL and elevated blood pressure (P<0.05 for all). PCOS FHx was independently associated with prediabetes (P<0.05). We observed an independent association of PCOS FHx with clinical and biochemical hyperandrogenism (P<0.05 for all), whereas there was no independent association of T2DM FHx with hyperandrogenism. PCOS women with a positive FHx of both T2DM and PCOS had an adverse metabolic and endocrine profile including a linear increase in risk of obesity, central fat accumulation, MS, prediabetes and low HDL (P<0.05 for all). Conclusions Our findings suggest that the assessment of FHx might allow risk stratification of PCOS women, which is important considering the high prevalence of PCOS.
Gesehen am 01.09.2020